Process design and simulation study of an electricity generation plant utilizing low-grade wasted thermal energy using aspen Hysys software - Janter Pangaduan Simanjuntak; Binsar Maruli Tua Pakpahan; Purwantono Purwantono; Khaled Ali Al-attab (Universitas Negeri Padang, 2023)
An analysis of the operational parameters of a small-scale electrical generation facility that uses the thermal energy contained in the flue gases from rubbish waste incineration is the goal of this study. To assess this system, the organic Rankine cycle (ORC) thermodynamic system was used. Since the organic fluid has a lower boiling point than water and can be evaporated with less thermal energy, it was chosen as a heat transfer medium instead of water. Aspen Hysys was utilized as a simulation tool, while R11 was used as the working fluid. To maximize the amount of available electrical output power, the plant's operational temperature, working fluid flow rate, and pressure are all maximized. According to the simulation's findings, flue gas may generate electric power between the ranges of 3.12 – 29.71 kW at working pressures between 2.5 and 3.5 bar and working fluid flow rates between 3.600 and 7200 kg/h when the temperature is between 50 and 95 oC. The system reaches a thermal efficiency of about 8.30 at 350 kPa of working fluid pressure.